Wyniki badań na stanowisku kultury pucharów lejkowatych Początkowo 36, gmina Aleksandrów Kujawski - Rzepecki, Seweryn (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
The site Poczałkowo 36 is situated in a valley of the Tążyna river which runs across the north eastern part of Kujawy. The presented material comes from two excavation operations. The first (detailed surface excavations) took place in the year 1980. The second (rescue excavations) were conducted in 1997. The site turned out to be damaged to a large degree. The disproportion between the quantity of material achieved during the surface examinations (— ........ ceramic items and 36 Hint items) and a number of finds uncovered as the result of deep excavations (85 items of ceramic and 2 flint items) is an evident prove of the above statement. In the light of these studies the collection from the site Poczałkowo 36 should be dated to the II phase of the funnel cups culture in Kujawy. In the author’s opinion there is much evidence indicating that the site Poczałkowo 36 should be treated as a remnant of a relatively short-term settlement. This opinion may cast new light on the structure of raw material of flint relics. Domination of finds made of the Baltic flint might suggest a relatively late dating of uncovered collections and could be connected with a relatively short period of functioning of a given site (assuming that flint and ceramic relics vary in case of short-term settlements (camps), where the raw material was gained casually ) from the relics found in long term (stable) settlements.